Diagnosis of apical hypertrophic cardiomyopathy using magnetic resonance imaging. Issue 1 (1st January 2000) - Ibrahim, T; Schwaiger, M
Abstract : Apical hypertrophic cardiomyopathy is an uncommon variant of non-obstructive hypertrophic cardiomyopathy with low prevalence outside East Asia. A case is reported of a non-Asian (European) 51 year old man with characteristic ECG and morphological changes of apical hypertrophic cardiomyopathy. Although the patient underwent catheterisation three years previously because of suggested coronary ischaemic heart disease, apical hypertrophic cardiomyopathy was not diagnosed. More recently, a regional wall motion abnormality was noticed at the apex on echocardiography. To rule out an ischaemic injury a stress perfusion scintigraphy was performed; no perfusion defect was present but an apical tracer enhancement was noted. Further evaluation by magnetic resonance imaging revealed the pathognomonic "ace of spades" configuration of the left ventricle with systolic obliteration of the apical region, which led to the diagnosis of apical hypertrophic cardiomyopathy.